Ventriculoperitoneal Shunt Peritoneal Catheter Knot Formation - Anwar Ul-Haq; Faisal Al-Otaibi; Saud Alshanafey; Mohamed Diya Sabbagh; Essam Al Shail (Case Reports in Neurological Medicine)
The ventriculoperitoneal (VP) shunt is a common procedure in pediatric neurosurgery that carries a risk of complications at cranial and abdominal sites. We report on the case of a child with shunt infection and malfunction. The peritoneal catheter was tethered within the abdominal cavity, precluding its removal. Subsequently, laparoscopic exploration identified a knot at the distal end of the peritoneal catheter around the omentum. A new VP shunt was inserted after the infection was healed. This type of complication occurs rarely, so there are a limited number of case reports in the literature. This report is complemented by a literature review.